DESIGNING SMARTHOME THROUGH INTERNET NETWORKING USING RASPBERRY PI COMPUTER - Tri Aristi Saputri; Sofyan Rofiq (Bakti Nusantara Institute, 2018)
Human activity is now increasing rapidly, causing human beings to often leave home. With such busy activities, someone will have difficulty communicating with his/her electronical equipment at home. Electronical equipment at home can be controlled using internet network and through website called smarthome. The smarthome can facilitate the users in controlling their home electronical appliances such as lights, fans, and so forth. So as to reduce the waste of electricity when users forget to turn off their electronical equipment when they are outside the home or wherever the users are. Smarthome uses a raspberry pi computer that serves as a server that will connect between hardware and software controlled through the website as an interface that users use to enter input and generate output. The making of this web uses Raspbian operating system where the software used is python and HTML. The method used in developing software is waterfall method according to Sommerville. The features on this website are 16 buttons, if the button is green then the electronic equipment is on, and if the button is black then the electronic equipment is off.